INTERNALISASI NILAI-NILAI MORAL AGAMA PADA ANAK USIA DINI - Sapendi Sapendi (AT-TURATS, 2015)
As the next generation of the family and the nation, children need to obtain good education so that their personal potential can develop, and they will grow to be strong and have a wide range of useful abilities and skills. It is therefore important for the family and educational institutions to take part in and be responsible for providing a wide variety of stimulation and guidance that will create a tough future generation. Childhood, especially at an early age or between 0 to 8 years, is often called the golden years, because in this stage, various abilities of children grow rapidly. Giving appropriate stimulation and facilities in this phase will greatly affect the subsequent process of their development. In contrast, when the environment around them such as parents, educators, and society fail to provide appropriate stimulation to their abilities, they will not grow as expected. Internalization of moral and religious values help to increase and guide the development of children. Establishment of moral and religious values in children is not merely a routine worship activities, but rather it should be instilled in a direct, concrete way and appropriate to a child’s language in the conduct of daily life. Introducing moral and religious values since early childhood will hopefully be a guide for him in the future.